PENDAMPINGAN PEMBUATAN NOMOR INDUK BERUSAHA (NIB) UNTUK PENGEMBANGAN UMKM MILIK MAHASISWA BINAAN FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS AIRLANGGA: Indonesia - Agustina, Tri Siwi; Sutrisno, Destina Tri Hutami (Jurnal Abdimas Madani dan Lestari (JAMALI), 2024)
A Nomor Induk Berusaha (NIB) is essential for business owners, especially those who are developing their businesses because NIB can preserve the legality and integrity of a product. However, many business owners need to realize the importance of having an NIB. In this regard, the author was motivated to assist student-owned MSMEs, a program by the Faculty of Economics and Business, Airlangga University, to obtain a NIB. Business owners can register on the online system through the Online Single Submission (OSS) website to obtain an NIB. In this research, we will discuss how to obtain an NIB through the online system and the benefits of helping several students who owned businesses aided by the Faculty of Economics and Business, Airlangga University, to obtain a NIB. The study results show that the OSS web application provides valuable information. Business owners can apply for an NIB without changing their business permits or operations by activating an OSS account, filling out company data in the OSS system, completing the information on previously owned licenses, after which the OSS system will issue an NIB for the business owners.